Fabrication of barium hexaferrite nanocomposite and hybrid multiwalled carbon nanotubes/barium hexaferrite as microwave absorbing material - Rosdi, Nurshahiera (2022)
This research work studied the synthesis of barium hexaferrite (BHF) in detail, focusing on their microstructure, magnetic, and microwave properties. As the raw material for this project, the iron (III) oxide, Fe2O3, is utilized and processed from mill scale waste. The iron (III) oxide, Fe2O3, then mixed with barium carbonate (BaCO3) to synthesize the barium hexaferrite (BaFe12O19, BHF) by employing the high-energy ball milling (HEBM) technique for 3 hours, a single milling (SM) process. The BHF-SM samples were then sintered from 800 °C to 1400 °C with an increment of 100 °C. The sintered BHF-SM samples was again employing by HEBM technique for 3 hours, a double milling (DM) process. The samples after double millng process namely as BHF-DM. The hybrid multiwalled carbon nanotubes (MWCNTs)/BHF has been introduced in this research. The structural, microstructure and magnetic properties of the prepared samples were examined using an X-ray diffractometer (XRD), vibrating sample magnetometer (VSM), and field emission scanning electron (FESEM), respectively. Vector network analyzer (VNA) has been used for measuring Reflection Loss (RL), complex permeability (µr) and complex permittivity (εr) in frequency ranges at X and Ku band (8-18 GHz). The RL for BHF-SM and BHF-DM nanocomposites are samples sintered at 1400 oC, shows the maximum RL with −13.71 dB is at the frequency of 9.96 GHz with a bandwidth of 0.24 GHz at a thickness of 3 mm and −35.57 dB at 12.33 GHz with a bandwidth of 1.2 GHz at a thickness of 2 mm, respectively. The hybrid MWCNTs/BHF-SM sample with 10 wt% filler content could enhance the RL values up to −43.99 dB at a frequency of 12.96 GHz with bandwidth of 2.56 GHz at a thickness of 2 mm. As for hybrid MWCNTs/BHF-DM sample, the RL is approximately −32.49 dB at 12.9 GHz with a bandwidth of 2.31 GHz at a thickness 2 mm. Generally, it was found that hybrid is a most highly potential candidate as ideal MAMs due to high microwave attenuation performances, enhanced the RL of and wide bandwidth.